2014
DOI: 10.14800/ics.530
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous inflammation and myogenic cell migration limit muscle tissue regeneration mediated by acellular scaffolds

Abstract: Volumetric muscle loss (VML) following orthopaedic trauma results in chronic loss of strength and can contribute to disability. Tissue engineering and regenerative medicine approaches to regenerate the lost skeletal muscle and improve functional outcomes are currently under development. At the forefront of these efforts, decellularized extracellular matrices (ECMs) have reached clinical testing and provide the foundation for other approaches that include stem/progenitor cell delivery. ECMs have been demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Decellularized ECM is a scaffold prepared by removing cells from source mammalian tissue or whole organs, leaving behind the native ECM with preserved structural and chemical composition. Decellularized ECM has been used as a biomaterial because it contains the native ligands, ECM proteins, and growth factors found in skeletal muscle which are known to play an instrumental role in SC chemotaxis and proliferation, the inflammatory response, myotube differentiation and, ultimately, functional tissue regeneration [63,[127][128][129]. These ECM molecules include collagens, laminin, fibronectin, heparin sulfate, chondroitin sulfate, HA, VEGF, FGF2, and TGF-β [130][131][132][133].…”
Section: Biophysical Cuesmentioning
confidence: 99%
“…Decellularized ECM is a scaffold prepared by removing cells from source mammalian tissue or whole organs, leaving behind the native ECM with preserved structural and chemical composition. Decellularized ECM has been used as a biomaterial because it contains the native ligands, ECM proteins, and growth factors found in skeletal muscle which are known to play an instrumental role in SC chemotaxis and proliferation, the inflammatory response, myotube differentiation and, ultimately, functional tissue regeneration [63,[127][128][129]. These ECM molecules include collagens, laminin, fibronectin, heparin sulfate, chondroitin sulfate, HA, VEGF, FGF2, and TGF-β [130][131][132][133].…”
Section: Biophysical Cuesmentioning
confidence: 99%
“…Looking forward, the defects created in VML injuries are large, empty, amorphous gaps in the muscle tissue. Promoting adequate proliferation of satellite cells and myogenic progenitors are one of the major challenges of VML repair [4,7,26,47]. Implantation of autologous satellite cells in vivo have proven inefficient due to low viability and survival post-implantation [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…The D-ECM scaffolds containing key basement membrane structural proteins, growth factors, and glycosaminoglycans (GAG) have been shown to support vascularization and functional recovery post-VML injury [4,17,[22][23][24][25]. However, D-ECM scaffolds have been unable to regenerate muscle fiber following VML appreciably, and often result in fibrotic tissue deposition (reviewed in [26]). In a rodent muscle VML injury model, transplantation of a decellularized porcine UBM resulted in fibrotic scar tissue deposition with little to no muscle fiber regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Particular consideration was given to the response of monocytes to polymer films of Studies of poly(ε-caprolactone)-scaffolds [56] and polydioxanone-scaffolds [57] showed that increased hydrophilicity and elasticity exerted favorable effects on this type of cells.…”
Section: A Study Of Hemocompatible Properties Of Phasmentioning
confidence: 99%